2017
DOI: 10.1016/j.powtec.2017.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Computational fluid dynamics analysis of the Venturi Dustiness Tester

Abstract: Dustiness quantifies the propensity of a finely divided solid to be aerosolized by a prescribed mechanical stimulus. Dustiness is relevant wherever powders are mixed, transferred or handled, and is important in the control of hazardous exposures and the prevention of dust explosions and product loss. Limited quantities of active pharmaceutical powders available for testing led to the development (at University of North Carolina) of a Venturi-driven dustiness tester. The powder is turbulently injected at high s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 63 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…In this framework, dustiness has risen as a valuable tool for occupational safety (Hamelmann & Schmidt, 2003), as it is a measure of a material's tendency to generate airborne dust during handling. However, discussions are ongoing about the use of the dustiness index as a direct predictor for worker exposure (Dubey et al, 2017;Fonseca et al, 2018) because dust emissions are known to depend on powder properties, the amount of material handled, the process, and local controls (Fransman et al, 2011). Certain authors (Brouwer, 2006;Class et al, 2001;Fonseca et al, 2018;Heitbrink et al, 1990) found no clear or limited relationship between exposure and dustiness, although they pointed out the importance of this parameter for risk assessment.…”
Section: Introductionmentioning
confidence: 99%
“…In this framework, dustiness has risen as a valuable tool for occupational safety (Hamelmann & Schmidt, 2003), as it is a measure of a material's tendency to generate airborne dust during handling. However, discussions are ongoing about the use of the dustiness index as a direct predictor for worker exposure (Dubey et al, 2017;Fonseca et al, 2018) because dust emissions are known to depend on powder properties, the amount of material handled, the process, and local controls (Fransman et al, 2011). Certain authors (Brouwer, 2006;Class et al, 2001;Fonseca et al, 2018;Heitbrink et al, 1990) found no clear or limited relationship between exposure and dustiness, although they pointed out the importance of this parameter for risk assessment.…”
Section: Introductionmentioning
confidence: 99%
“…The VDT was selected due to its ability to utilize small quantities of powder (5 mg) under confined conditions (Boundy, Leith, and Polton 2006;Evans et al 2013). This small aerosol chamber is ideal for dealing with hazardous powders, as it uses small quantities of material to generate a reproducible aerosol within an enclosed set-up and has been validated experimentally to provide reproducible results (Boundy, Leith, and Polton 2006;Evans et al 2013;Evans et al 2014;Dubey, Ghia, and Turkevich 2017). The VDT aerosolization method involves more aggressive airflows than those typically encountered in large-scale workplace activities, but is expected to resemble energetic dust dispersion activities such as the use of compressed air to clean contaminated protective clothing or work surfaces (Evans et al 2013).…”
Section: Aerosolization Methodsmentioning
confidence: 99%
“…The first type of uncertainty estimation is conducted through the use of Grid Convergence Index (GCI) method proposed by Celik et al [29]. This method has been evaluated and implemented in several hundred CFD studies [30][31][32][33]. In order to estimate GCI, Case 3 (Table 4) was simulated on three different grids (Cases 4 & 5), which are shown in Table 7.…”
Section: Grid Independence Studymentioning
confidence: 99%